SmartPLS Application for Evaluating Cybersecurity Resilience in University of Raharja IT Infrastructure - Ari Asmawati; Nita Hermawati; Citra Tesalonika Karisma; Diana Ayu; Aditya Ilham Setyobudi; Muhammad Adi Alyano (International Institute for Advanced Science & Technology (IIAST), 2024)
In the ever-evolving landscape of digital security, educational institutions face heightened challenges in safeguarding sensitive information. This study explores network security factors within the IT infrastructure of University of Raharja, emphasizing the utilization of SmartPLS as an analytical tool. The research adopts an exploratory descriptive design, encompassing diverse stakeholders to comprehensively analyze technical and human-centric aspects of network security. SmartPLS, a Partial Least Squares (PLS) path modeling software, serves as the primary analytical tool, evaluating the impact of Technical Infrastructure, User Awareness and Training, and Incident Response and Management on Network Security Effectiveness. Findings reveal strong internal consistency and reliability across key variables, emphasizing the interconnected nature of incident response management, SmartPLS implementation, technical infrastructure, and user awareness and training. Structured surveys, in-depth interviews, and system log analysis contribute to a holistic understanding of network security challenges. The study not only provides insights for University Raharja but offers valuable findings applicable to similar educational institutions. The research underscores the efficacy of SmartPLS in unraveling the intricate dynamics of network security within the academic domain. This study contributes to informed decision-making for fortifying digital ecosystems in educational institutions against evolving cyber threats.